Me, You, and Us Affective Education Module - Rodriguez, Ana Maria; Baptiste, H. Prentice, Jr.; Houston Univ., TX. Coll. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Designed to foster affective growth in elementary school students, this learning module has two purposes: to provide structured small group activities which will allow children to become more aware of who they are, what they value, and how they relate with their peers and others; and to provide an opportunity for children to develop self-acceptance and a respectful acceptance of those who are different from them, culturally and otherwise. Although this module is designed for implementation with fourth, fifth, and sixth grade students, the same activities are adaptable to any grade level. Each session requires approximately 45-60 minutes for completion and features activities designed for small groups of 8 to 12 members. The module contains 10 sessions which can be implemented once a week, 2 or 3 times a week, or every day, depending upon the needs of the students and teacher. Each session consists of a statement of purpose, objectives, materials and resources needed, teaching procedure, learning activities (enabling activities), and evaluation procedure. The Piers-Harris Children's Self-Concept Scale is administered as a pre-post test measure to determine entry and exit points. At the end of the 10 sessions, students write essays about their feelings concerning the importance of learning about others and working with them. Students also give an oral evaluation of each session. (Author/CM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Differences; Curriculum Guides; Elementary Education; Group Activities; Humanistic Education; Humanization; Individual Differences; Instructional Materials; Learning Activities; Learning Modules; Mexican Americans; Multicultural Education; Peer Acceptance; Pretests Posttests; Self Actualization; Self Concept; Student Evaluation; Values Clarification; Piers Harris Childrens Self Concept Scale; Guides, Classroom -- Teacher